Performance Assessment of Selected Farmer Managed Irrigation System in Kaski District, Nepal - Gautam, Arjun (Himalayan Journal of Applied Science and Engineering, 2020)
The performance of three Irrigation System (IS); Arva Ghari, Tirkang Kimbesi and Hemja Sinchai Pranali was assessed using the Focus Group Discussion (FGD) and structured interview. The IS situated in the Kaski district were managed by users committee which were mainly formed by the election. The water availability is sufficient in upstream and decreases towards downstream leading to tail end deprivation, however, there was no dominance of influential person in water allocation. Proper distribution system minimizes the conflict among the users which depends on the condition of the canal along with regulating structures. The deposits of silt on bed and vegetation on banks have reduced the discharge capacity which needs the regular maintenance for the better performance of the IS. Separate fund should be raised for the repair and maintenance of canal. FMIS should be supported to strengthen its capacity as these are yet to be institutionalized and genuine farmers should be encouraged to participate for the management of the IS.